Enhanced electrocatalytic activity of low-cost NiO microflowers on graphene paper for the oxygen evolution reaction. Issue 19 (8th September 2022) - Bruno, Luca; Scuderi, Mario; Priolo, Francesco; Mirabella, Salvo
Abstract : Oxygen evolution reaction driven by NiO microflowers. Abstract : Electrochemical water splitting represents a promising source of renewable energy. Since electrochemistry is a useful method, it should be fast and cost-effective. However, the half-reaction for the oxygen evolution reaction (OER) represents a limiting factor because of its slow kinetics and large energy barrier. Typically, although critical raw materials such as IrO2 and RuO2 can be used as catalysts, sustainable and efficient catalysts are urgently required. Among oxides of transition metals, NiO represents a promising candidate as a high-performance catalyst for the oxygen evolution reaction. Here, a low-cost, high-throughput, environmentally friendly chemical methodology is used to produce NiO microflowers composed of very thin sheets (20 nm thick) intertwined like petals of a desert rose, as shown by electron microscopy and X-ray diffraction analysis. These microflowers, dispersed onto a graphene paper substrate by spin coating or drop casting, were carefully tested as electrocatalysts for the OER. The optimized electrode based on the NiO microflowers exhibited an overpotential of 314 mV at a current density of 10 mA cm −2 under alkaline conditions (1 M KOH). The intrinsic activity of the catalyst was evaluated by measuring the Tafel plot (as low as 40 mV dec −1 ) and turnover frequencies (0.01 or 6.98 s −1 for bulk or redox determination). The reported results prove that Ni based nanostructures are promising materials for efficient anodes in sustainable water splitting electrocatalysis.